A zipped-up tunable metal coordinated cationic polymer for nanomedicine. Issue 7 (10th February 2020) - Mao, Jianming; Wang, Jianwei; Tang, Guping; Chu, Paul K.; Bai, Hongzhen
Abstract : The zipped-up polymer MCCP shows applications in diverse aspects of nanomedicine with tunability. Abstract : Incorporating metal elements into polymers is a feasible means to fabricate new materials with multiple functionalities. In this work, a metal coordinated cationic polymer (MCCP) was developed. Ferric ions were incorporated into the polyethyleneimine-β-cyclodextrin (PC) polymer chain via coordination to produce a zipped-up polymer with a micro-ordered and macro-disordered topological structure. By varying the metal concentration, a tunable superstructure could be formed on the nano-templates via the "zipping" effect. In addition, the physicochemical properties of the assembly of MCCPs and nucleic acids were tailored by tuning the composition of the metal ions and polymers. The loading efficiency of Rhodamine-B by MCCPs was enhanced. The in vitro and in vivo results showed that the hybrid materials could be adjusted to deliver nucleic acids or small molecules with good performance and acquired the capacity of generating reactive oxygen species in tumor cells. Thus, the tunable and multifunctional MCCP system has great potential in nanomedicine and biomaterial science.